Nanomedicines to Treat Skin Pathologies with Natural Molecules - Esposito, Elisabetta; Nastruzzi, Claudio; Sguizzato, Maddalena; Cortesi, Rita (Current Pharmaceutical Design, 2019)
The skin and mucous membranes are subjected to many disorders and pathological conditions. Nature offers a wide range of molecules with antioxidant activity able to neutralize, at least in part, the formation of free radicals and therefore to counteract the phenomena of cellular aging. Since synthetic drugs for the treatment of skin diseases can induce resistance, it is particularly interesting to use compounds of plant origin, transporting them in pharmaceutical forms capable of controlling their release and absorption. This review provides an overview of new findings about the use of lipid-based nanosystems for the delivery of natural molecules useful on the topical treatment of skin disorders. Several natural molecules encapsulated in lipid nanosystems have been considered in the treatment of some skin pathologies or diseases. Particularly, the use of rosemary and eucalyptus essential oil, saffron derivatives, curcumin, eugenol, capsaicin, thymol and lycopene has been reported. The molecules have been alternatively encapsulated in viscous systems, such as the organogels, or in liquid systems, such as ethosomes, transferosomes, solid lipid nanoparticles and monoolein based dispersions thickened by inclusion in carbomer gels. The nanostructured forms have been in vitro and in vivo investigated for the treatment of skin disorders due to dehydration, inflammation, melanoma, wound healing, fungal infections or psoriasis. The data reported in the different studies have suggested that the cutaneous application of lipid nanosystems allows a deep interaction between lipid matrix and skin strata, promoting a prolonged release and efficacy of the loaded natural molecules. This review suggests that the application of natural molecules onto the skin by lipid-based nanosystems can provide numerous clinician benefits in dermatology and cosmetics.
Keywords: nanotechnology